Synthesis and properties of a novel narrow band gap oligomeric diketopyrrolopyrrole-based organic semiconductor. (August 2016) - Le Borgne, Mylène; Quinn, Jesse; Martín, Jaime; Stingelin, Natalie; Wantz, Guillaume; Li, Yuning
Abstract: A trimer of diketopyrrolopyrole (DPP), Tri-BTDPP, was synthesized and characterized. Tri-BTDPP has a HOMO level of −5.34 eV, a low band gap of 1.33 eV, and a hole mobility of ∼10 −3 cm 2 V −1 s −1 in organic field effect transistors (OFETs). Organic photovoltaic (OPV) devices using the donor/acceptor blends of Tri-BTDPP and PC71 BM exhibited low power conversion efficiencies (PCE) of up to 0.72%, even though the desirable optical and electronic characteristics of this compound as a donor semiconductor for achieving high performance for OPV. Through an intensive study of the active layer using AFM, XRD, and DSC, it was found that Tri-BTDPP and PC71 BM were unable to intermix and formed oversized Tri-BTDPP phases, resulting in poor charge separation. Some guidance on how to improve the OPV performance of Tri-DPP compounds is provided. Highlights: A new trimer of diketopyrrolopyrole (DPP), Tri-BTDPP, is synthesized. Tri-BTDPP has favorable optoelectronic properties for organic photovoltaics (OPV). Blend films of Tri-BTDPP and PCBM are studied and evaluated in OPV.